2019
DOI: 10.23958/ijirms/vol04-i01/550
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mesothelial Marker Calretinin in Breast Cancer

Abstract: Calretinin (CR) is a calcium binding protein of calmodulin superfamily, a widely used marker for mesothelial differentiation. It is also found to be expressed in breast carcinoma. Breast carcinoma is the leading cause of cancer death in women and despite new approaches and advances, it is still difficult to predict the behaviour of the tumour and its prognosis. So there is a need and struggle to identify new markers for prognosis of breast cancer. The study is aimed at evaluating the frequency of Calretinin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Our study has shown results similar to the study by Aboobacker et al [17] as both the studies has been conducted in a low study population whereas the other studies compared shows a higher study population which can explain the significant correlation.The study by Farrag et al [19] has showed maximum number of cases under grade I and II and among these cases maximum showed low expression and the grade III tumours, maximum showed high calretinin expression (p<0.05).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study has shown results similar to the study by Aboobacker et al [17] as both the studies has been conducted in a low study population whereas the other studies compared shows a higher study population which can explain the significant correlation.The study by Farrag et al [19] has showed maximum number of cases under grade I and II and among these cases maximum showed low expression and the grade III tumours, maximum showed high calretinin expression (p<0.05).…”
Section: Discussionsupporting
confidence: 90%
“…The study by Aboobacker et al [17] also showed no significant correlation between age and Calretinin expression (p>0.05). Another study by Faraag et al [14] showed that calretinin expression is independent of age of the patient.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations